Whose models? Which representations? A response to Wagner - Hardman, Doug (Journal of medical ethics, 2023)
In Where the Ethical Action Is, we argued that medical and ethical modes of thought are not different in kind but different aspects of a situation. One of the consequences of this argument is that the requirement for or benefits of normative moral theorising in bioethics is undercut. In response, Wagner has argued that normative moral theories should be reconceived as models. Wagner’s argument seems to be that once reconceived as models, the rationale for moral theorising, undercut by our arguments in Where the Ethical Action Is, will be re-established because we will see those moral-theories-now-rebranded-as-models as serving a role akin to the role models serve in some of the natural sciences. In this response to Wagner, we provide two arguments against Wagner’s proposal. We call these arguments the Turner-Cicourel Challenge and the Question Begging Challenge.